The Impact of Powder Delivery Process Parameters on Spreading Behaviour in Powder Bed Fusion Additive Manufacturing - Bruno Nicola Dose; Sina Zinatlou Ajabshir; Ali Hassanpour; Diego Barletta; Massimo Poletto (Chemical Engineering Transactions)
In this study, the effects of spreading speed and bed temperature on powder spreading in the Laser-Beam Powder Bed Fusion (PBF-LB) process were investigated. A purposely developed image analysis method was used to evaluate powder spread quality. High-resolution macro images covering most of the powder layer (10×7 cm) were captured and processed to obtain a wavelet power spectrum to highlight the distribution of roughness wavelengths on the layer surface. Results showed that increasing spreading speed and bed temperature widened the spectral density distribution of roughness wavelengths. The Spreadability Index (SI), defined as the ratio of the median particle size to the dominant surface wavelength, decreased by 7% when the temperature rose from 25 °C to 80 °C at a spreading speed of 3 mm/s. At a constant temperature of 25 °C, increasing the spreading speed from 3 mm/s to 30 mm/s reduced the SI by 64%, highlighting the significant impact of spreading speed on powder quality.